The Impact of Containment Measures and Monetary and Fiscal Responses on US Financial Markets during the Covid-19 Pandemic - Emmanuel Joel Aikins Abakah; Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper analyses the effects of containment measures and monetary and fiscal responses on US financial markets during the Covid-19 pandemic. More specifically, it applies fractional integration methods to analyse their impact on the daily S&P500, the US Treasury Bond Index (USTB), the S&P Green Bond Index (GREEN) and the Dow Jones (DJ) Islamic World Market Index (ISLAM) over the period 1/01/2020-10/03/2021. The results suggest that all four indices are highly persistent and exhibit orders of integration close to 1. A small degree of mean reversion is observed only for the S&P500 under the assumption of white noise errors and USTB with autocorrelated errors; therefore, market efficiency appears to hold in most cases. The mortality rate, surprisingly, seems to have affected stock and bond prices positively with autocorrelated errors. As for the policy responses, both the containment and fiscal measures had a rather limited impact, whilst there were significant announcement effects which lifted markets, especially in the case of monetary announcements. There is also evidence of a significant, positive response to changes in the effective Federal funds rate, which suggests that the financial industry, mainly benefiting from interest rises, plays a dominant role.
Keywords: C22; C32; G15; 330; Covid-19; policy responses and announcements; containment measures; US financial markets; stocks; bonds; Islamic stocks; green bonds